ANALYSIS OF PRODUCTION COST CALCULATION USING THE VARIABLE COSTING METHOD AT PT. SUMBER TANI AGUNG (PKS SABUNGAN) - Ferdi Dermawan Nasution; Marliyah Marliyah; Fauzi Arif Lubis (International Journal of Cultural and Social Science, 2025)
PT Sumber Tani Agung Resources has implemented a systematic financial recording system as a commitment to accountability and transparency. However, the researcher's observations indicate that production cost reports have not yet classified costs in detail, particularly in separating fixed and variable costs. This study aims to analyze the calculation of the cost of goods manufactured (COGS) using the Variable Costing method as an alternative to the company's current method. The study was conducted using a qualitative descriptive approach through observation, interviews, and document studies at PT Sumber Tani Agung (PKS Sabungan). The results show that the COGS calculated using the company's method is higher than the Variable Costing method. This difference is caused by the company's treatment of fixed overhead costs, which are included entirely in COGS, while the Variable Costing method only considers variable costs as a component of production. The difference in value between the two methods is Rp 14,017,007.00 per month, which can affect the accuracy of selling price determination and profit planning. These findings emphasize the importance of implementing appropriate cost accounting principles to support effective managerial decision-making. This study provides practical contributions for companies in evaluating COGS calculation strategies as well as academic implications in managerial accounting studies.